Correlation between CT phenotypic patterns with clinical, nutritional and pulmonary function parameters among COPD patients - Dogra, Vikas; Menon, Balakrishnan; Bansal, Vishal; Gaur, Shailendra Nath (International Journal of Research in Medical Sciences, 2018)
Background: COPD is a multi-dimensional disorder with multiple phenotypes. The commonly used GOLD guidelines and Spirometry do not fully reflect the heterogeneous nature of the disease, structural abnormalities, and phenotypes. This necessitates CT phenotyping because of difference in treatment strategies, disease progression and response to treatment. Methods: We conducted our study on 40 male COPD subjects aged more than 45 years, divided them into 4 groups based on CT phenotype as normal, Airway Dominant (AD), Emphysema Dominant (ED) and mixed types. We compared the clinical parameters, spirometry indices, markers of nutrition (including BMI) across these phenotypes. CT phenotypes were determined by Low Attenuation Area (LAA) and Wall area. Results: In our study, 16 (40%) had airway dominant (AD), 15 (37.5%) had emphysema dominant (ED), 4 (10%) had mixed, and 5 (12.5%) had normal CT phenotype. The various nutrition indicators like height, weight, BMI, fat-free mass index was not statistically significant. The difference in the median FEV1/FVC across CT phenotypes was statistically significant (P Value 0.002). The difference in Haemoglobin, Total protein, Albumin, Triglycerides and Total Cholesterol was not statistically significant across CT Phenotypes. Conclusions: The GOLD guidelines do not fully reflect the heterogeneous nature of the disease which necessitates CT phenotyping. In our study, there was a significant association between BMI, FEV1/FVC ratio with CT phenotypes. Identifying the different phenotypes of COPD will allow us to implement a more personalized treatment and choose the best treatment option.